Standard Operating Procedure (SOP) for Sailor's Book Sign On/Sign Off Management at KSOP Class 1 Dumai At PT. Putra Andalas Samudera Dumai - Samuel Nababan; Dirhamsyah Dirhamsyah; Netty Kesuma (Journal of Management and Social Sciences, 2024)
Putra Andalas Samudera is a company that operates in the field of domestic and overseas agents, PT. Putra Andalas Samudera provides ship entry and exit licensing services, certificate extensions, and management of sign on and sign off seafarers' books. The data collection methods used by the author in writing this paper are the field observation method (field research) and the library research method. This paper aims to determine the process of managing the sign on/off book for ship crew sailors at PT. Putra Andalas Samudera, the process began after a direction from the owner that there would be a crew change activity, after that the process of signing on the crew's seaman's book went to the KSOP class 1 Dumai office. Signing on/off in the sailor's crew book is very important for a seafarer, apart from being a sign that the seafarer has legally joined the ship, it also adds to the seafarer's work experience. The problems faced in the process of signing on/off the crew sailor's book were the delay in information from the owner to sign on the crew's sailor's book which resulted in hampering the clearance process. Good cooperation and coordination between shipping companies and related agencies in signing on/off seafarers' books is very necessary for smooth service to crew document handlers. It is important to remember that the purpose of coordination is so that the relevant agencies can carry out their duties and functions smoothly, safely and efficiently.